Synthesis, Characterization, and Magnetic Studies of α-Fe2O3 Nanoparticles. (28th January 2014) - Arora, Avnish Kumar; Sharma, Mohan; Kumari, Ritu; Jaswal, Vivek Sheel; Kumar, Pankaj
Abstract : Very fine nanosized metal oxide, namely, iron oxide ( α -Fe2 O3 ) has been synthesized by precipitation method using ammonia as precipitating agent and characterized by using XRD (X-ray diffraction), TGA/DTA, surface area measurement, transmission electron microscopy (TEM), and magnetic measurements techniques. XRD studies show that iron oxide was formed as α -Fe2 O3 instead of the commonly formed magnetite nanoparticles (Fe3 O4 ) or a mixture of magnetite (Fe3 O4 ) and maghemite ( γ -Fe2 O3, cubic), and it has rhombohedral structure. Magnetic measurements showed that iron oxide has five unpaired electrons and is ferromagnetic in nature, Ms value being 1.7 emu/g. The particle size of the synthesized iron oxide was determined by TEM. TEM images show that the size of particles of Fe2 O3 varied from 15 nm to 49 nm with average crystallite size 35 nm.